Control of diamondback moth with Lippia gracilis essential oil - Oliveira, Joseane de Jesus (2022)
The objective of this work was to evaluate the potential of the essential oils of the LGRA-106 and LGRA-108 Lippia gracilis genotypes for the control of diamondback moth (Plutella xylostella). The lethal concentrations (LCs) were estimated by two routes of action (residual and spraying), using oil concentrations ranging from 0.5 to 3.0% v v-1, diluted in Tween 80 (1.5%). To determine the effect of the LC to 50% (LC50) on the development of P. xylostella, two compounds of the L. gracilis genotypes, thymol, and carvacrol, were sprayed on the insects. The repellency of the LC50 was evaluated by residual action, in a free-choice behavioral bioassay. The LGRA-106 genotype showed a greater toxicity via residual action (LC50 = 8.82 mg mL-1), as well as a higher repellency index. LGRA-108 was more toxic via spraying (LC50= 9.64 mg mL-1). Larval development and viability were reduced in approximately 50% with LGRA-106 or thymol and up to 70% with LGRA-108 or carvacrol, which caused mortality from 1.70 to 1.97 days after spraying. The oils of the LGRA-106 and LGRA-108 genotypes of L. gracilis have insecticidal activity in the control of P. xylostella.